(untitled) (Journal of Economic Research & Business Administration, 2019)
The authors systematized the theoretical concepts of identifying bankruptcy risks, proposed to identify the risks of bankruptcy by assessing the crisis of internal processes. The indicators of the crisis of management of agricultural organizations are summarized. The crisis of management is primary in relation to other processes that cause the risk of bankruptcy. The assessment of indicators of crisis of management in the agricultural organizations of the Orenburg region is given. For the purpose of diagnostics of crisis processes grouping of the agricultural organizations of the Buzuluk district of the Orenburg region was executed. The identifiers of this crisis are the profitability of production costs, return on assets, the ratio of growth rates of accounts receivable and accounts payable. The scientific novelty of the research lies in the formation of management information in the context of business processes and responsibility centers to determine indicators of bankruptcy risks, as well as in the development of elements of management reporting, which allows to assess the activities of responsibility centers for financial recovery of agricultural organizations. Financial recovery in this article is considered as a pre-trial procedure, which is the interaction of responsibility centers in the conditions of mobilization of internal resources for the purpose of development of production, increase of financial results and prevention of financial insolvency.